Review of vehicular emission problems in Singapore - Lee, Chiou Kang. (2008)
This review studies the various systems that have been implemented and their impact on the control of vehicular emission. It also looks at the direction in which Singapore will be heading towards a clean air environment where vehicular emission is no longer a major source of pollution.